Circadian Rhythms and Mitochondria: Connecting the Dots - Sardon Puig, Laura; Valera-Alberni, Miriam; Cantó, Carles; Pillon, Nicolas J. (Frontiers in Genetics, 2018)
Circadian rhythms provide a selective advantage by anticipating organismal nutrient needs and guaranteeing optimal metabolic capacity during active hours. Impairment of circadian rhythms is associated with increased risk of type 2 diabetes and emerging evidence suggests that metabolic diseases are linked to perturbed clock machinery. The circadian clock regulates many transcriptional–translational processes influencing whole cell metabolism and particularly mitochondrial activity. In this review, we survey the current literature related to cross-talks between mitochondria and the circadian clock and unravel putative molecular links. Understanding the mechanisms that link metabolism and circadian responses to transcriptional modifications will provide valuable insights toward innovative therapeutic strategies to combat the development of metabolic disease.